2022
DOI: 10.1038/s41746-021-00552-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in vascular surgery: a systematic review and critical appraisal

Abstract: Machine learning (ML) is a rapidly advancing field with increasing utility in health care. We conducted a systematic review and critical appraisal of ML applications in vascular surgery. MEDLINE, Embase, and Cochrane CENTRAL were searched from inception to March 1, 2021. Study screening, data extraction, and quality assessment were performed by two independent reviewers, with a third author resolving discrepancies. All original studies reporting ML applications in vascular surgery were included. Publication tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“… 28 Our group recently reported a systematic review of ML applications in vascular surgery and identified 212 studies using ML techniques for diagnosis, prognosis, and image segmentation in carotid stenosis, aortic aneurysm/dissection, peripheral artery disease, diabetic foot ulcer, venous disease, and renal artery stenosis. 29 AI/ML can be used to achieve the goals of improving efficiency in clinical practice by learning from large amounts of data to make automated predictions to guide clinical decision-making. 30 The advantage of using ML models is that they can quickly analyze large amounts of data, including a patient’s demographic information, medical history, previous clinical encounters, and imaging data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 28 Our group recently reported a systematic review of ML applications in vascular surgery and identified 212 studies using ML techniques for diagnosis, prognosis, and image segmentation in carotid stenosis, aortic aneurysm/dissection, peripheral artery disease, diabetic foot ulcer, venous disease, and renal artery stenosis. 29 AI/ML can be used to achieve the goals of improving efficiency in clinical practice by learning from large amounts of data to make automated predictions to guide clinical decision-making. 30 The advantage of using ML models is that they can quickly analyze large amounts of data, including a patient’s demographic information, medical history, previous clinical encounters, and imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…32 A systematic review of ML applications in vascular surgery included 212 relevant studies on diagnosis, prognosis, and image segmentation for six major vascular conditions with good predictive value. 29 The participants reported that AI/ML would be most useful in research and education, reflecting that this technology remains in the research and development phase, with limited applications in routine clinical settings. As AI/ML algorithms become deployed clinically, the perceptions of vascular surgeons regarding areas in which the technology could be helpful could evolve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main domains include telemedicine/ telehealth, mobile applications (also called “m-health”), the development of smart devices such as sensors and wearables, the use of digital technology for healthcare information system or the development of integrated networks, and all are potentially enhanced using AI techniques [ 1 , 6 ]. Digital health represents a considerable potential for improving the management of vascular diseases and has attracted growing interest for clinicians, researchers, patients, companies, institutional and policy makers, as shown by an exponential increase in academic publications [ 7 , 8 ]. A substantial growth of the global market for digital health could be observed over the past decade [ 9 ].…”
mentioning
confidence: 99%